Antiretroviral Drugs and Risk of Chronic Alanine Aminotransferase Elevation in Human Immunodeficiency Virus (HIV)-Monoinfected Persons: The Data Collection on Adverse Events of Anti-HIV Drugs Study. (21st January 2016) - Kovari, Helen; Sabin, Caroline A.; Ledergerber, Bruno; Ryom, Lene; Reiss, Peter; Law, Matthew; Pradier, Christian; Dabis, Francois; d'Arminio Monforte, Antonella; Smith, Colette; de Wit, Stephane; Kirk, Ole; et al.
Abstract: Background.  Although human immunodeficiency virus (HIV)-positive persons on antiretroviral therapy (ART) frequently have chronic liver enzyme elevation (cLEE), the underlying cause is often unclear. Methods.  Data Collection on Adverse Events of Anti-HIV Drugs (D:A:D) Study participants without chronic viral hepatitis were observed to the earliest of cLEE (elevated aminotransferase ≥6 months), death, last follow-up, or January 2, 2014. Antiretroviral treatment exposure was categorized as follows: no exposure and ongoing short- and long-term exposure (<2 or ≥2 years) after initiation. Association between development of cLEE and ART exposure was investigated using Poisson regression. Results.  Among 21 485 participants observed for 105 413 person-years (PY), 6368 developed cLEE (incidence 6.04/100 PY; 95% confidence interval [CI], 5.89–6.19). Chronic liver enzyme elevation was associated with short-and long-term exposure to didanosine (<2 years rate ratio [RR] = 1.29, 95% CI, 1.11–1.49; >2 years RR = 1.26, 95% CI, 1.13–1.41); stavudine (<2 years RR = 1.51, 95% CI, 1.26–1.81; >2 years RR = 1.17, 95% CI, 1.03–1.32), and tenofovir disoproxil fumarate (<2 years RR = 1.55, 95% CI, 1.40–1.72; >2 years RR = 1.18, 95% CI, 1.05–1.32), but only short-term exposure to nevirapine (<2 years RR = 1.44, 95% CI, 1.29–1.61), efavirenz (<2 years RR = 1.14, 95% CI, 1.03–1.26), emtricitabine (<2 years RR = 1.18, 95% CI, 1.04–1.33), and atazanavir (<2 years RR = 1.20, 95% CI, 1.04–1.38). Chronic liver enzyme elevation was not associated with use of lamivudine, abacavir, and other protease inhibitors. Mortality did not differ between participants with and without cLEE. Conclusions.  Although didanosine, stavudine, nevirapine, and efavirenz have been described to be hepatotoxic, we additionally observed a consistent association between tenofovir and cLEE emerging within the first 2 years after drug initiation. This novel tenofovir-cLEE signal should be further investigated.